If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r = (b + -7) * m Reorder the terms: r = (-7 + b) * m Reorder the terms for easier multiplication: r = m(-7 + b) r = (-7 * m + b * m) Reorder the terms: r = (bm + -7m) r = (bm + -7m) Solving r = bm + -7m Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Simplifying r = bm + -7m
| 51.56=4y+8x | | a^2+ay=33 | | 6a-(4-5a)=30 | | 6.28*X^2+37.68X=200 | | 5g-9g+8=20+2g | | m+6m+8=0 | | a^2+(-7-3)=23 | | .667x+5=1.667x | | X^2-89x-90=0 | | ay-7-3=23 | | x+6=7x+9 | | -12X+8=64 | | -0.3+r=4.2 | | -2(-3w+1)-7w=5(w-2)-8 | | 200=2*3.14*X^2+2*3.14*X*6 | | 200=2*(Pi)*X^2+2*(Pi)*X*6 | | -9(v+5)=-7v-37 | | 200=2*pi*X^2+2*pi*X*6 | | 2v-41=-3(v-3) | | -3(x-4)=-8x-13 | | 4x+3(x-6)=17 | | -32=2(v+4)+3v | | 4(y-7)-7y=2 | | -3=-5+2w | | 54x+29(442-x)=17568 | | 7+5(3x-3)=-2(4x-1)+8x | | A=xy*10x | | -3+5=-18 | | 14-6(6X-5)=5(2x-1)-4x | | 5y=-2x+0 | | 13=5u-7 | | -53-2l=-i+20 |